Low-power supralinear photocurrent generation via excited state fusion in single-component nanostructured organic photodetectors. Issue 19 (29th April 2022) - Antoniou, Giannis; Yuan, Peisen; Koutsokeras, Loukas; Athanasopoulos, Stavros; Fazzi, Daniele; Panidi, Julianna; Georgiadou, Dimitra G.; Prodromakis, Themis; Keivanidis, Panagiotis E.
Abstract : Columnar arrangement of triplet emitters in the photoactive layer of vertically-configured photodetectors enables photocurrent generation via triplet–triplet annihilation of dimer species. Abstract : The integration of triplet–triplet annihilation (TTA) components as electrically and optically active elements in vertically-configured photoactive device architectures is a challenging task to achieve. Herein we present a simple methodology for incorporating a photon absorbing layer of the (2, 3, 7, 8, 12, 13, 17, 18-octaethyl-porphyrinato)platinum(ii ) (PtOEP) metallorganic complex, as a self-TTA annihilator medium in a sandwich-like photodiode device structure. At low power illumination, the PtOEP photodiode exhibits photocurrent generation via the fusion of optically induced PtOEP excited states and it develops an open-circuit voltage ( V OC ) as high as 1.15 V. The structural and spectroscopic characterization of the nanostructured PtOEP photoactive layer in combination with electronic structure calculations identify PtOEP dimer species as the annihilating excited state responsible for the formation of charges. The participation of the fusion process in the mechanism of charge photogeneration manifests in the supralinear dependence of the short-circuit current density ( J SC ) on the incoming photoexcitation intensity, both when incoherent and coherent light are used for illuminating the PtOEP diodes. The photoresponse of the PtOEP device allows for highly selective and sensitive photodetection within the 500–560 nm narrow spectral range. At short-circuit conditions a power-law is observed in the dependence of the device responsivity on fluence. The observed response of the PtOEP photodiodes reveals a hitherto neglected mechanism of photocurrent generation in single-component organic electronic devices that is facilitated by TTA reactions. These findings pave the way towards the fabrication of next-generation electro-optical switches, ultrasensitive organic photodetectors, and TTA-sensitized solar cells with vertically-configured device structure.